Gold : - Lewis, Nathan (John Wiley & Sons, 2007)
For most of the last three millennia, the world's commercial centers have used one or another variant of a gold standard. It should be one of the best understood of human institutions, but it's not. It's one of the worst understood, by both its advocates and detractors. Though it has been spurned by governments many times, this has never been due to a fault of gold to serve its duty, but because governments had other plans for their currencies beyond maintaining their stability. And so, says Nathan Lewis, there is no reason to believe that the great monetary successes of the past four centuries, and indeed the past four millennia, could not be recreated in the next four centuries. In Gold, he makes a forceful, well-documented case for a worldwide return to the gold standard. Governments and central bankers around the world today unanimously agree on the desirability of stable money, ever more so after some monetary disaster has reduced yet another economy to smoking ruins.